2014 IEEE Fourth International Conference on Big Data and Cloud Computing 2014
DOI: 10.1109/bdcloud.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Social Networking Site in the Facilitation of Internationalization in Higher Education: A Case Study Using the Actor Network Theory Perspective

Abstract: Internationalization is a growing area in world-wide higher education. In order for local and international students to develop into responsible global citizens, they need to interact while they are on the university campus together. With the aim of facilitating local and international student interaction, a Facebook Page was set up by the international office at a university. The page was monitored over a two and a half year period to see what types of interactions would occur and Actor Network Theory was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Overall, a majority of the review articles confirmed the existence of the key ANT components found in the proposed framework (green coloured) and were generally aligned with the proposed sequencing of these components. Furthermore, the review revealed the existence of additional socio-technical dynamics such as de-enrolment [61]; re-problematisation [61,70]; competing problematisations [11,65,68]; ongoing problematisations [44]; focal actors as OPPs [70,77]; and allies [66], all of which were beyond the scope of this study.…”
Section: Figure 6: Proposed Ant Application Frameworkmentioning
confidence: 94%
See 3 more Smart Citations
“…Overall, a majority of the review articles confirmed the existence of the key ANT components found in the proposed framework (green coloured) and were generally aligned with the proposed sequencing of these components. Furthermore, the review revealed the existence of additional socio-technical dynamics such as de-enrolment [61]; re-problematisation [61,70]; competing problematisations [11,65,68]; ongoing problematisations [44]; focal actors as OPPs [70,77]; and allies [66], all of which were beyond the scope of this study.…”
Section: Figure 6: Proposed Ant Application Frameworkmentioning
confidence: 94%
“…Nineteen per cent of the case studies involved problems and solutions that are specific to information technology [60,62,71,73,76]. Other case studies were related to privatisation [64], technology infrastructure [67,77], higher education management [11,74], forestry [68], online user authenticity [72], intellectual capital [70], and technology usage [66]. These concepts might not be immediately relevant to the tools and techniques associated with industrial engineers; however, the processes in these fields could be suitable for engineering science.…”
Section: Application Of Ant In Problem Identification and Solution Im...mentioning
confidence: 99%
See 2 more Smart Citations